2019
DOI: 10.1093/cid/ciz1164
|View full text |Cite
|
Sign up to set email alerts
|

Dose-specific Effectiveness of 7- and 13-Valent Pneumococcal Conjugate Vaccines Against Vaccine-serotype Streptococcus pneumoniae Colonization in Children

Abstract: Background Reduced-dose pneumococcal conjugate vaccine (PCV) schedules are under consideration in countries where children are recommended to receive 3 doses. Whereas PCV-derived protection against vaccine-serotype colonization is responsible for herd effects of vaccination, dose-specific PCV effectiveness against colonization endpoints is not known. We aimed to assess the performance of differing PCV schedules against vaccine-serotype colonization in children. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 37 publications
2
13
1
Order By: Relevance
“…35 A study from Brazil reported a similar VE with three primary doses of PCV13 at 44.0% (14.2%-63.5%) against VT carriage among children 7-11 months of age, 36 while a study from Israel found a VE of 62% (95% CI 33% to 83%) against PCV13 carriage among children 25-59 months of age. 37 Our results were also lower than estimates of VE for PCV13 from modelling in Malawi, at 66.87% (95% CI 50.49% to 82.26%). 38 The differing estimates may relate to the timing of assessment after vaccine is administered to each child (ie, waning direct effects), since a meta-regression of original efficacy results from PCV7 trials reported VEs ranging from 62% (95% CI 52% to 72%) 4 months after vaccination to 42% (95% CI 19% to 54%) 5 years after vaccination.…”
Section: Bmj Global Healthcontrasting
confidence: 73%
See 1 more Smart Citation
“…35 A study from Brazil reported a similar VE with three primary doses of PCV13 at 44.0% (14.2%-63.5%) against VT carriage among children 7-11 months of age, 36 while a study from Israel found a VE of 62% (95% CI 33% to 83%) against PCV13 carriage among children 25-59 months of age. 37 Our results were also lower than estimates of VE for PCV13 from modelling in Malawi, at 66.87% (95% CI 50.49% to 82.26%). 38 The differing estimates may relate to the timing of assessment after vaccine is administered to each child (ie, waning direct effects), since a meta-regression of original efficacy results from PCV7 trials reported VEs ranging from 62% (95% CI 52% to 72%) 4 months after vaccination to 42% (95% CI 19% to 54%) 5 years after vaccination.…”
Section: Bmj Global Healthcontrasting
confidence: 73%
“…Samples were screened for the presence of pneumococci using quantitative real-time PCR (qPCR) targeting the lytA gene. 19 Samples that were lytA qPCR positive (Ct value <35) or equivocal (Ct value [35][36][37][38][39][40] were cultured for molecular serotyping of pneumococcal isolates by microarray. Samples with Ct >40.0 were considered negative for pneumococcus.…”
Section: Laboratory Proceduresmentioning
confidence: 99%
“…The reason for the failure of immunoprophylaxis against serotype 3 S. pneumoniae has not been determined yet. Some studies have suggested that the carriage rate of serotype 3 S. pneumoniae might have played an important role: there was no significant decrease, but even an upward trend in the number of carriers ( Azarian et al., 2018 ; Lewnard et al., 2019 ; Madhi et al., 2020 ). Others suggested that the special characteristics of type 3 capsular polysaccharide may also be an important factor ( Choi et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative, VE can be estimated by comparing the odds of vaccination and pathogen detection among controls against the "null" odds of vaccination within the control group, irrespective of pathogen detection (20). Such an approach may be advantageous when pathogen…”
Section: Notation and Theoretical Frameworkmentioning
confidence: 99%
“…As an alternative, VE S can be estimated by comparing the odds of vaccination and pathogen detection among controls against the “null” odds of vaccination within the control group, irrespective of pathogen detection (20). Such an approach may be advantageous when pathogen detection data are available only from a subset of all control individuals from whom vaccination data are available (e.g., in the case of expensive or invasive diagnostic procedures (21,22)), or when favored by other design considerations.…”
Section: Vaccine Direct Effect Against Shedding or Carriage Of The Pamentioning
confidence: 99%